Development and evaluation of the first fertility preservation patient decision aid to support boys and young men with cancer: The Cancer, Fertility and Me for Boys and Young Men research protocol. - Bob Phillips; Richard Anderson; Anne-Mairead Folan; Georgina Louise Jones; Sheila Lane; Allan Pacey; Rod Thomas Mitchell; Brendan Gough; Danielle Sarah Musson; Nicola O’Donnell; Abigail Lewis; Maximilian Williamson; et al. (BMJ Open)
Introduction Many cancer treatments can result in reduced fertility, impacting survivors’ opportunities for biological parenthood. Fertility preservation (FP) methods for boys and young men, such as cryopreservation of testicular tissue or sperm, offer hope but are currently underused among young male patients with cancer. Despite guidelines recommending early discussion of fertility implications, many newly diagnosed males do not receive FP counselling or referral to fertility services. Male cancer survivors face a higher likelihood of infertility than their peers, yet focused FP decision-making support is lacking. This study aims to address this gap by developing and evaluating the first dedicated patient decision aid (PtDA) for boys and young male patients with cancer aged 11–25 years old, to help them make informed FP decisions before receiving cancer treatment.Methods and analysis The current study follows a multistage process: developing the PtDA, alpha testing for acceptability with former patients, parents and healthcare professionals, and beta testing in clinical settings to ensure effective integration into routine care. Using a combination of interviews and questionnaire data, this research will assess the PtDA’s acceptability and impact on decision-making.Ethics and dissemination This study has been prospectively registered on the Research Registry (10273). Ethics approval has been obtained from Leeds Beckett University and the National Health Service/Health Research Authority before undertaking data collection. The final resource will be disseminated widely and made freely available online via our dedicated Cancer, Fertility and Me website, for use in clinical and research practice.